Methods of the analysis of motion of small space vehicles around the centre of masses at deployment of space tether system. (1st January 2014) - Zabolotnov, Yuriy; Naumov, Oleg
This paper studies analytical and numerical methods of the analysis of spatial motion concerning centre of mass of small space vehicles at deployment of space tether system. Deployment of space tether system is executed from the base space vehicle. The set angular orientation of the base space vehicle concerning a local vertical is provided by means of own system of stabilisation. The small space vehicle (or freight) represents a descent capsule returned to the Earth or the space vehicle transferred into higher orbit. It is supposed that the weight of the base space vehicle is much more than weight of freight. The angular position of freight is described by classical Euler's angles determined concerning a direction of a tether. Analytical methods of the analysis of angular motion are based on an averaging method (for small angles of nutation) and on a method integral of manifolds which allows to investigate the nonlinear equations of angular motion of freight. The major factors influencing stability of angular motion of freight concerning a direction of a tether are considered. Results of numerical modelling of angular motion of the small space vehicle are presented.